Mr PENDAMPINGAN BELAJAR ANAK MI/SD DENGAN PENDEKATAN FUN LEARNING DI TPQ AL BAROKAH SEKERIKIL KELURAHAN PARAKAN KAUMAN DENGAN METODE ABCD: PENDAMPINGAN BELAJAR ANAK MI/SD DENGAN PENDEKATAN FUN LEARNING DI TPQ AL BAROKAH SEKERIKIL KELURAHAN PARAKAN KAUMAN DENGAN METODE ABCD - prada, yoga; wildan, Mukhamad Khouf; Pratiwi, Fenika; Rizky Mafaza, Dania; Al Hakim, Muhammad Fadloli (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2025)
Children's cognitive development involves progressive learning processes such as attention, memory or recall, and logical thinking.Learning assistance is a guidance process that aims to help children understand subject matter, complete tasks, and increase learning motivation through a personalized and contextual approachThe Asset Based Community Development (ABCD) method is a community-based development approach that focuses on exploring and utilizing local assets or potential to create sustainable change. This method involves structured stages that include discovery, dream, design, define, and destinyThe discovery stage is the first step to recognize the potential and strengths of TPQ Al Barokah, both in terms of students and programs that are already running Through the Dream stage, children are encouraged to feel more involved in the learning process at TPQ. The Design stage is designed to strengthen children's understanding of Islamic material. One of the activities is Islamic educational games that focus on fasholatan - The ABCD method can be effectively applied to support the learning assistance program for MI / SD children at TPQ Al Barokah - The fun learning approach is able to significantly increase santri involvement in the learning process at TPQ Al Barokah. By combining fun, interactive and experiential activities